Verteilungspolitische Herausforderungen der Corona-Krise (Wirtschaftsdienst, 2021)
The Coronavirus crisis has had a distinct impact on the labour market. The lockdown has led to job losses, especially in the catering and tourism industries. Certain sectors have also been affected by shortterm work. This also has consequences for the income situation of affected households. It is evident that households with incomes that were already lower before the crisis are more affected by income losses during the crisis. However, the federal government’s economic stimulus and crisis management aid package is certainly effective at stabilising jobs and averting social hardship. However, men benefit from this comparatively more than women.